ABA and GA 3 increase carbon allocation in different organs of grapevine plants by inducing accumulation of non-structural carbohydrates in leaves, enhancement of phloem area and expression of sugar transporters - Murcia, Mauro German; Pontin, Mariela Ana; Reinoso, Herminda; Baraldi, Rita; Bertazza, Gianpaolo; Gomez Talquenca, Gonzalo; Piccoli, Patricia Noemí; Bottini, Ambrosio Rubén (2017)
Grape quality for winemaking depends on sugar accumulation and metabolism in berries. Abscisic acid (ABA) and gibberellins (GAs) have been reported to control sugar allocation in economically important crops, although the mechanisms involved are still unknown. The present study tested if ABA and gibberellin A3 (GA3) enhance carbon allocation in fruits of grapevines by modifying phloem loading, phloem area and expression of sugar transporters in leaves and berries. Pot-grown Vitis vinifera cv. Malbec plants were sprayed with ABA and GA3 solutions. The amount of soluble sugars in leaves and berries related to photosynthesis were examined at three points of berry growth: pre-veraison, full veraison and post-veraison. Starch levels and amylase activity in leaves, gene expression of sugar transporters in leaves and berries and phloem anatomy were examined at full veraison. Accumulation of glucose and fructose in berries was hastened in ABA-treated plants at the stage of full veraison, which was correlated with enhancement of Vitis vinifera HEXOSE TRANSPORTER 2 (VvHT2) and Vitis vinifera HEXOSE TRANSPORTER 6 (VvHT6) gene expression, increases of phloem area and sucrose content in leaves. On the other hand, GA3 increased the quantity of photoassimilates delivered to the stem thus increasing xylem growth. In conclusion, stimulation of sugar transport by ABA and GA3 to berries and stems, respectively, was due to build-up of non-structural carbohydrates in leaves, modifications in phloem tissue and modulation in gene expression of sugar transporters.